Persepsi Pelanggan, Situasi Pelayanan dan Citra Puskesmas berhubungan dengan Kepuasan Pasien: Customer Perception, Service Conditions, and Community Health Center Image Are Associated with Patient Satisfaction - Mutiara Nandini; Zulfikri Mukarom, Muhammad; Rizky Ramadhani , Nur (Journal of Public Health Education, 2024)
Introduction: The health center is a service sector that is able to work directly with the community and provide health services through health services by providing treatment, preventing disease, curing and restoring health. Patient satisfaction with health center services is related to good guarantees, service quality, and responsiveness. Dissatisfaction with service procedures, as well as the comfort of the service environment can make patients not return to the health center and have a major influence on the satisfaction of outpatients at the health centerObjectives: The purpose of this study was to determine the relationship between customer perception, service situation and health center image on patient satisfaction at the SKJ Depok Health Center in 2024. Method: Quantitative research method with a cross sectional research design. The sample in this study was outpatients at the Community Health Center, totaling 60 respondents. The data used is primary data distributed through a questionnaire. Data analysis was carried out univariate and bivariate using the chi-square test. Result: the results of the study, it shows that there is a relationship between customer perception with p-value = 0.013 (p <0.05), there is a relationship between service situations with p-value = 0.000 (p <0.05), there is a relationship between the image of the health center with p-value = 0.020 (p <0.05) with patient satisfaction at the SKJ Depok Health Center. Conclution: There is a relationship between customer perception, service situations and the image of the health center on patient satisfaction at the SKJ Depok Health Center in 2024.